Pemekaran Jemaat: Sebuah Analisis Teologi-Sosial di Jemaat GPM Passo - Markus Janes Huliselan (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2021)
This article aims to analyze the problem of conflict that occurred due to the division of the congregation in the Maluku Protestant Church (GPM). In particular, the Congregation of Passo became the locus of research. Using qualitative descriptive, the researcher found data from congregants against and pro of church expansion. This research used the functional perspective on social conflict from Lewis A. Coser to analyze various conflict variables in the Passo Congregation. I found that the conflict in Passo was influenced by multiple external factors, such as an understanding of the customary land, the perspective of the urban community, the relationship between the church and local government, and the interests of local politicians. The church's mission in the world is to build a peaceful fellowship. Therefore, this article finally proposes a theological perspective on the community of peace as a theological approach in understanding the issue of conflict between congregations.